2022
DOI: 10.1007/s00701-022-05432-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis in penetrating traumatic brain injury: analysis of a single-center series and systematic review of the literature

Abstract: Purpose Penetrating traumatic brain injury (pTBI) is an acute medical emergency with a high rate of mortality. Patients with survivable injuries face a risk of infection stemming from foreign body transgression into the central nervous system (CNS). There is controversy regarding the utility of antimicrobial prophylaxis in managing such patients, and if so, which antimicrobial agent(s) to use. Methods We reviewed patients with pTBI at our institution and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 34 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…However, based on the published studies, some indications are clear. No significant differences in infection rates exist between patients who received AP and those who did not 11–21 . No differences were observed between basilar or skull close and open fractures 22 .…”
Section: Definitionsmentioning
confidence: 81%
See 1 more Smart Citation
“…However, based on the published studies, some indications are clear. No significant differences in infection rates exist between patients who received AP and those who did not 11–21 . No differences were observed between basilar or skull close and open fractures 22 .…”
Section: Definitionsmentioning
confidence: 81%
“…No significant differences in infection rates exist between patients who received AP and those who did not. [11][12][13][14][15][16][17][18][19][20][21] No differences were observed between basilar or skull close and open fractures. 22 Data showed heterogeneity in terms of inclusion criteria, duration of antibiotic therapy, and dosages.…”
Section: Definitionsmentioning
confidence: 99%
“…For example, the minimization of lines could be achieved through a consolidation of prophylactic antibiotics. The triple-antibiotic regimen was initiated on arrival, but a single coverage with cefazolin may be appropriately used for aerobic and anaerobic agents in the setting of penetrating ballistic injury [12,34]. In severe TBIs, mild induced hypothermia (35-36°C) has been considered to offer benefits in reducing the cerebral metabolic rate of oxygen while patients are prevented from shivering (via sedation/paralytic medications) [35].…”
Section: Discussionmentioning
confidence: 99%
“…He was intubated, sedated, and taken urgently for right-sided decompressive craniectomy followed by external ventricular drain (EVD) placement for intracranial pressure monitoring. En route to the operating room, he received mannitol (1 g/kg); tranexamic acid 1 gm; triple antibiotic coverage including vancomycin, metronidazole, and cefepime [12]; levetiracetam for seizure prophylaxis; and propofol for sedation. The triple antibiotics were administered in accordance with the department protocol.…”
Section: Cth: Computed Tomography Of the Headmentioning
confidence: 99%
“…[ 10 ] The decision to administer prophylactic antibiotics to TBI patients is largely based on previous guidelines and the preferences of neurosurgeons. [ 3 ] In a study conducted by Marut et al .,[ 6 ] it was found that 24 out of 33 patients received prophylactic antibiotics, and none of these 33 patients experienced central nervous system infections.…”
Section: Discussionmentioning
confidence: 99%